Women's perceptions of cardiovascular risk after preeclampsia: a qualitative study - Lene Musfelt Nielsen; Maria Guldbrandt Hauge; Anne S. Ersbøll; Marianne Johansen; Jesper James Linde; Peter Damm; Karoline Kragelund Nielsen (BMC, 2022)
Abstract Background Preeclampsia is associated with increased risk of cardiovascular disease later in life, but studies suggest that women with previous preeclampsia are not aware of this. Little is known about how these women perceive the condition and the associated long-term risks. We examined the experiences and perceptions of preeclampsia and the increased risk of cardiovascular disease (CVD) later in life among Danish women with previous preeclampsia and their attitudes towards CVD risk screening. Methods Ten individual semi-structured interviews were conducted with women with previous preeclampsia. Data were analysed using thematic analysis. Results We identified six themes: 1) Experiences and perceptions of being diagnosed with preeclampsia, 2) Awareness about increased risk of CVD later in life, 3) Knowledge as a precondition for action, 4) The perception of CVD risk as being modifiable, 5) Motivators for and barriers to a healthy lifestyle, and 6) Screening for CVD. Awareness of the severity of preeclampsia was limited prior to being diagnosed. Particularly among those with few or no symptoms, preeclampsia was perceived as a non-severe condition, which was further reinforced by the experience of having received very little information. Nonetheless, some women were shocked by the diagnosis and feared for the health of the offspring. Many women also experienced physical and psychological consequences of preeclampsia. Awareness of the increased risk of later CVD was lacking; yet, when informed, the women considered this to be essential knowledge to be able to act accordingly. The risk of future CVD was perceived to be partly modifiable with a healthy lifestyle, and the women expressed a need for counselling on appropriate lifestyle changes to reduce CVD risk. Other factors were also mentioned as imperative for lifestyle changes, including social support. The women were generally positive towards potential future screening for CVD because it could provide them with information about their health condition. Conclusions After preeclampsia, women experienced a lack of knowledge on preeclampsia and the increased risk of CVD later in life. Improved information and follow-up after preeclampsia, including guidance on CVD risk reduction and support from health professionals and family, are warranted.